Diálogo entre história e literatura em Um Rio Chamado Tempo, Uma Casa Chamada Terra, de Mia Couto - Lisboa, Leiri Dayana Barbosa Silva (2016)
Throughout the time, many borders were raised and intensified antagonism between literature and history. At the same time, the explanatory models that have defined this knowledge passed to be questioned. The limits between science and art, the erudite and the popular as well as the relations of knowledge and power were problematized and they gave to reason and to the reality a greater importance, to the detriment of subjectivity and scientific fiction watched by per si, to establish an intimate process between literature and history. And it is through these discussions focused on the correlation between these two areas of knowledge, we have developed this work, taking as object of study the literary work Um rio chamado tempo, uma casa chamada terra, of the Mozambican Mia Couto. Narrative which shows echoes of the Mozambican literary tradition, targeted by the materiality of the world, is other words, for economic reasons, subjective, inter-subjective of power and by historical perspectives of culture, without forgetting to show the permeability of literature and real (story), seeking constructive and innovative dialogue, rather contaminated by memory. To establish the discussion on African literature, especially Mozambican, we sought grounds on Maria Fernanda Afonso, Ana Mafalda Leite, Pires Laranjeiras, among others. It is also adhere to the theoretical framework guiding principles of Postcolonial Studies of hybridization notions colonialism and present the ideas of its main authors like Albert Memmi, Homi Bhabha, Frantz Fanon and Stuart Hall. Then we detached the literary text of the encounter with history, drawing on Aristotles thoughts, in order to demonstrate that a fictional work is not limited only to tell what happened, but to observe what could have happened too, from the perspective verisimilitude. Hayden White also helps us to state that the plurality of meanings of literary and historical texts accrue from contextualization, in a view of, there is a dynamic that specifies the literary art and the construction of the historical text, wich adrheres, it transforms or breaks theirs significant loads, through a polysemic speech, intentionally, and, in most cases, selective.